Effect of rock mass properties on blast-induced rock fragmentation. (2016) - Choudhary, Bhanwar Singh; Sonu, Kumar; Kishore, Keshav; Anwar, Shahid
Blasting converts the in-situ rock mass into a muck pile with appropriate shape, looseness and fragment size distribution suitable for subsequent downstream processes of loading, hauling, crushing, grinding. The fragment size distribution of blasted rock material is used in the mining industry as an index to estimate the effect of bench blasting. To investigate the influence of rock mass properties on fragmentation in bench blast, the degree and size distribution of fragments within a blasted rock mass is essential. This study presents the result of the effects of rock mass properties on rock fragmentation. Fragalyst® computer software was deployed to analyse the captured images for joint and fragmentation analysis. From the study it was found that the mean fragment size increases with increase in porosity, strength and in-situ block size but it decreases with increase in rock density for the given field constraints.